Sistem Pengelolaan Sanggar Pendidikan Seni di Lombok Timur - Murcahyanto, Hary (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to find out how the management of art education centers in East Lombok Regency. This research uses a qualitative approach with a qualitative descriptive method. This research used three data collection techniques: interviews, observation, and documentation. While data analysis was carried out through four stages: data collection, data reduction, data presentation, and data verification. The results of this study are, the management system of art education studios in East Lombok consists of an organizational form, articles of association, and bylaws as well as administration which contains data on administrators, students, infrastructure, correspondence, and work programs. The production system of each art studio which includes training activities, training materials, training techniques, making works, and performance has been running well but still needs improvement. Several activities and initiatives are carried out in East Lombok to develop arts and culture. Arts education centers in East Lombok are influenced by various factors, including creativity, quality of education, financial support, market access, social environment, and technology. The conclusion of this research is that the management of art education studios in East Lombok has a legal and incorporated organizational system, a production system that has been running even though it is not optimal, and a management system and productivity that is quite good. Keywords: Arts centers. Arts education, Management